Plate Pack Structural Integrity Analysis for Plate and Shell Heat Exchangers at High Temperatures and Pressures - Noh Hyun-Seok; Cho Jong-Rae; Song Seung-Hun (Advances in Mechanical Engineering, 2020)
Heat exchangers capable of withstanding high temperature and pressure are required to achieve increased thermal efficiency and compactness. A welded plate and shell heat exchanger, developed for applications involving pressures up to 150 bar and temperatures up to 600 °C, has exhibited advantages that allow a more wide use of heat exchangers. However, few studies have tested the structural integrity of the plate pack of this design. In this paper, the structural integrity of the heat transfer pack was tested using finite element analysis. Elastic and elastic-plastic models were applied for one set of heat transfer plates, while layers of two and four plates were used to verify the effect of the boundary conditions. The plate results were evaluated according to the ASME Boiler and Pressure Vessel Code, Section VIII Division 2. Finally, the function of the end plate in the plate packs was numerically studied.